Factors associated to stunting children aged 6-24 Months in Yogyakarta - Nurul Qomariyah; Fia Amorita Dinasty Putri (Universitas Ahmad Dahlan, 2020)
Stunting is the impaired growth and development resulting from poor nutrition, repeated infection, and inadequate psychosocial stimulation. Children are defined as stunted if their height-for-age is more than two standard deviations below the WHO Child Growth Standards median. Purwomartani is a village with the highest prevalence of stunting in Kalasan (27.66%), Sleman, Special Region Yogyakarta. The aim of the study was to determine factors that are associated with the incidence of stunting in Purwomartani. Â Observational analytic research was conducted with a case-control design. Data was taken from the Nutrition Monitoring data of Kalasan primary health centre in 2018. Cases were children aged 6-24 months who experienced stunting (n=37). Control was children aged 6-24 months who are not stunted (n=37). Three respondents were excluded from each group. A total of 68 data was analyzed. The results of the study showed that the majority of those who are stunted are in the age groups 13-24 months and the gender was female. Variables related to the incidence of stunting were father's education (OR = 3.429; CI = 1,176-9,994), maternal education (OR = 3,519; CI = 1,270-9,750), birth weight (OR = 5,250; CI = 1,509-18,268) and breastfeeding history (OR = 3.378; CI = 1,246-9,157). Variables that were not related to the incidence of stunting are family income (OR = 1,486; CI = 0,540-4,084), maternal age (OR = 1,170; CI = 0,390-3,512) and birth interval (OR = 2.2750.799-6.476). Â Factors related to stunting were father's education, mother's education, birth weight and history of breastfeeding.